Efficacy and Safety of Oral Acetaminophen for Premature Infants With Patent Ductus Arteriosus: A Meta-Analysis - Xie Zi-Yun; Zhang Ruo-lin; Xia Yue-wei; Bo Tao (Frontiers Media S.A., 2022)
Objective: To systematically review the efficacy and safety of oral Acetaminophen for premature infants with patent ductus arteriosus (PDA).Methods: Databases including Ovid, EMbase, Pubmed, The Cochrane Library, Cumulative Index to Nursing and Allied Health Literature (CINHAL), China National Knowledge Infrastructure (CNKI), Chinese Biomedical Database (CBM), WanFang Data, China Science and Technology Journal Database were searched to collect the randomized controlled trials (RCTs) about Acetaminophen for premature infants with PDA from inception to January 1, 2021. Quality assessment was performed through bias risk evaluation according to the Cochrane Handbook 5.1.0, and then the homogeneous studies were analyzed using Revman 5.4 software.Results: A total of 16 RCTs were included, which were divided into for four subgroups: subgroup I (oral acetaminophen vs. oral ibuprofen, 13 RCTs), subgroup II (oral acetaminophen vs. intravenous indomethacin, 1 RCT), subgroup III (oral acetaminophen vs intravenous ibuprofen, 1 RCT), and subgroup IV (oral acetaminophen vs intravenous placebo, 1 RCT). In subgroup I, There was no significant difference in the ductal closure rate after the first course of drug administration [typical relative risk (RR) 0.97, 95% confidence interval (CI) 0.90 to 1.05], the accumulated ductal closure rate after two course of treatment (RR 0.96, 95% CI 0.91-1.02), and mortality (RR 1.06, 95% CI 0.75-1.49) between treatment with oral acetaminophen versus oral ibuprofen (p > 0.05); compared with oral ibuprofen, oral acetaminophen was associated with a significant reduction in the incidence of gastrointestinal bleeding/stool occult blood positive (RR 0.51, 95% CI 0.32 to 0.82)and oliguria (RR 0.62, 95% CI 0.42-0.91) (p < 0.05).Conclusion: The meta analysis approves the facts that there is no significant difference in the efficacity in premature infants with PDA between oral acetaminophen and buprofen or indometacin, but compared to ibuprofen, oral acetaminophen may decrease the incidence of oliguria and gastrointestinal bleeding. More reliable conclusions should be made through large-size, multi-center, well-designed RCTs.